2015
DOI: 10.1101/019570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In VivoBlunt-End Cloning Through CRISPR/Cas9-Facilitated Non-Homologous End-Joining

Abstract: The ability to precisely modify the genome in a site-specific manner is extremely useful.The CRISPR/Cas9 system facilitates precise modifications by generating RNA-guided doublestrand breaks. We demonstrate that guide RNA pairs generate deletions that are repaired with a high level of precision by non-homologous end-joining in mammalian cells. We present a method called knock-in blunt ligation for exploiting this excision and repair to insert exogenous sequences in a homology-independent manner without loss of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 94 publications
(81 reference statements)
1
30
0
1
Order By: Relevance
“…Это может приводить к по тере или вставке нуклеотидов (индел-мутации), а также к нуклеотидным заменам. Частота Cas9-обусловленного мутагенеза обычно составляет несколько десятков про центов (Geisinger et al, 2016).…”
unclassified
“…Это может приводить к по тере или вставке нуклеотидов (индел-мутации), а также к нуклеотидным заменам. Частота Cas9-обусловленного мутагенеза обычно составляет несколько десятков про центов (Geisinger et al, 2016).…”
unclassified
“…Translocation through precise end joining was demonstrated for blunt end DSBs induced by Cas9WT [121]. Moreover, a recent study demonstrated a high percentage of precise end joining between two blunt end DSBs that generated genomic microdeletions in different cell types [120], lending further support to the idea that blunt ends generated by Cas9WT can be repaired through error-free NHEJ. It should be noted, however, that in the study by Geisinger et al [120] deletion of the intervening sequence would have prevented the iterative cycle of cleavage and repair induced by the nuclease [114].…”
Section: Overview Of Dna Repair Mechanismsmentioning
confidence: 49%
“…Moreover, a recent study demonstrated a high percentage of precise end joining between two blunt end DSBs that generated genomic microdeletions in different cell types [120], lending further support to the idea that blunt ends generated by Cas9WT can be repaired through error-free NHEJ. It should be noted, however, that in the study by Geisinger et al [120] deletion of the intervening sequence would have prevented the iterative cycle of cleavage and repair induced by the nuclease [114]. Upon further examination of the data in that report, the range of precise ligation was higher in H9 pluripotent stem cells (>75 per cent, except for one guide RNA) than in HEK 293 cells (which varied between 44 per cent and 90 per cent), despite a similar repair pattern in both cell types.…”
Section: Overview Of Dna Repair Mechanismsmentioning
confidence: 79%
See 2 more Smart Citations